IMPLEMENTASI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DALAM KETERAMPILAN BERBICARA BAHASA ARAB - Muhsin; Dedy Wahyudin; Abdul Aziz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine 1) The Implementation of the Contextual Teaching and Learning (CTL) Approach in Arabic Speaking Skills, and 2) The Effectiveness of the Contextual Teaching and Learning (CTL) Approach in Arabic Speaking Skills. This research employs a mixed-method approach, combining both quantitative and qualitative methods. Data collection techniques used include interviews, observations and questionnaires. The results of this study indicate the successful implementation of the Contextual Teaching and Learning Approach in Arabic Speaking Skills, supported by several steps within the CTL framework. Furthermore, the use of the Contextual Teaching and Learning Approach in Arabic language learning effectively enhances the process of Maharah Kalam (Speaking Skills). This is demonstrated by the questionnaire distributed via Google Forms, which received a score of 80%.